2016
DOI: 10.15376/biores.11.4.8914-8928
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Co-digestion of Pig Manure with Dried Maize Straw

Abstract: The anaerobic co-digestion of pig manure (PM) with dried maize straw (DMS) was studied at 35 °C with a volatile solid (VS) ratio (VSPM/VSDMS) of 1:2 in a continuously stirred tank reactor, and the digestions of mono-PM and mono-DMS were evaluated under the same conditions. The organic loading rates (OLRs) of 2, 3, and 4 g VS/L/d were studied and found to correspond to hydraulic retention times (HRTs) of 60, 40, and 30 d, respectively. Under the condition of long HRT and low OLR, PM could be degraded completely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…The average value of the SMY obtained for PS substrate (farm 1 to 3) was 92 ±5 mL CH4/g VSadded, which is in accordance with data presented by Theofanous et al [38]. The difference observed in farm 4 (three times more) could be related to the higher TS of the slurry used as obtained in other authors studies [39]. The highest value (435 ±20 mL CH4/g VSadded) obtained for the PS sample collected at farm 5 could be explained once the experimental trial was implemented in situ with AcoD-mobile pilot Unit III.…”
Section: Mono-digestion Trialssupporting
confidence: 90%
See 1 more Smart Citation
“…The average value of the SMY obtained for PS substrate (farm 1 to 3) was 92 ±5 mL CH4/g VSadded, which is in accordance with data presented by Theofanous et al [38]. The difference observed in farm 4 (three times more) could be related to the higher TS of the slurry used as obtained in other authors studies [39]. The highest value (435 ±20 mL CH4/g VSadded) obtained for the PS sample collected at farm 5 could be explained once the experimental trial was implemented in situ with AcoD-mobile pilot Unit III.…”
Section: Mono-digestion Trialssupporting
confidence: 90%
“…Results obtained regarding AcoD trials with livestock manure used as substrateThe EPI value allows a simple comparison of the SMY values obtained in AD and AcoD experimental assays. As seen in Table4a(for LM) the EPI indicator ranged from 30% to 250% showing the advantages of ensuring the stability of AD process, by promoting a suitable C/N ratio and buffer capacity compared with mono-digestion trials (Table3a)[39]. Results obtained regarding AcoD trials with mixed SS used as substrate…”
mentioning
confidence: 95%
“…Biogas composition was measured using gas chromatography (Thermo Fisher, USA) with automatic sampler as described by Li et al ( 2014 ). Volatile fatty acids (VFAs) in digestate were determined by gas chromatography (Thermo Fisher, USA) with automatic sampler as described by Song et al ( 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Although the generation of revenue for the system depends on the number of pigs heads, high investment costs and inadequate business models result in few biogas plants installed in the country (Castro e Silva et al, 2021. Furthermore, some studies report high water and fiber contents might result in varied CH4 yields, hindering the stability of power generation (Costa Filho et al, 2017;Song et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…A study conducted by Castro e Silva et al ( 2020) proved economic feasibility (Net Present Value > 0) by producing 10,468 heads of pig, corresponding to an installed power of 14.69 kW, and energy generation of 102,972.83 kWh for 80% system operation in an agrobusiness system in the Southern of Minas Gerais State, Brazil. However, it is necessary to stress the influence of variability and low CH4 yields in the process, as well as the high content of water and fibers in pig excrement Song et al, 2016;Matulaitis et al, 2015;Jinadasa et al, 2012;Molinuevo et al, 2008). Some studies have reported increases in the efficiency of AD by adding trace elements derived from active minerals, resulting in more biogas production in function of the microorganic and enzymatic transformation during the entire process (Wilkie et al,1986;Parawira, 2012;Chai et al, 2013;Cruz Viggi et al, 2014;Liu et al, 2015;Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%